2021
DOI: 10.1112/blms.12473
|View full text |Cite
|
Sign up to set email alerts
|

Radon measures and Lipschitz graphs

Abstract: For all 1⩽m⩽n−1, we investigate the interaction of locally finite measures in Rn with the family of m‐dimensional Lipschitz graphs. For instance, we characterize Radon measures μ, which are carried by Lipschitz graphs in the sense that there exist graphs normalΓ1,normalΓ2,⋯ such that μ(double-struckRn∖⋃1∞normalΓi)=0, using only countably many evaluations of the measure. This problem in geometric measure theory was classically studied within smaller classes of measures, for example, for the restrictions of m‐di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…finiteness of their conical Dini function implies that is n-rectifiable. We would like to stress, however, that neither Theorem 1.4 implies the results from [7], nor the other way around.…”
Section: Rectifiabilitymentioning
confidence: 89%
See 2 more Smart Citations
“…finiteness of their conical Dini function implies that is n-rectifiable. We would like to stress, however, that neither Theorem 1.4 implies the results from [7], nor the other way around.…”
Section: Rectifiabilitymentioning
confidence: 89%
“…In Theorem D of [45], Naples showed that a modified version of (1.2) can be used to characterize pointwise doubling measures carried by Lipschitz graphs, that is, measures vanishing outside of a countable union of n-dimensional Lipschitz graphs. In an even more recent paper [7], Badger and Naples completely describe measures carried by n-dimensional Lipschitz graphs on R d . They use a Dini condition imposed on the socalled conical defect, and their condition is closely related to (1.4).…”
Section: Rectifiabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…It turns out that detecting m-dimensional rectifiability is more subtle for measures of Hausdorff dimension less than m than it is for measures of Hausdorff dimension m. Pointwise characterizations of locally finite measures on X that are carried by a family A (without restriction on dimension, doubling properties, or null sets of µ!) are presently available in two situations: (i) for measures on R n carried by rectifiable curves [15], and (ii) for measures on R n carried by m-dimensional Lipschitz graphs [11]. These results are made possible by a thorough understanding of subsets of rectifiable curves or Lipschitz graphs in R n and the incorporation of ideas from harmonic analysis.…”
Section: Introductionmentioning
confidence: 99%